Studies on the effect of Salvia aegyptiaca and Trigonella foenum graecum extracts on adult male mice - Amany A. Tohamy, Shaimaa R. Ibrahim and Ahmed E. Abdel Moneim (Journal of Applied Pharmaceutical Science)
Salvia aegyptiaca (Egyptian sage) and Trigonella foenum graecum (fenugreek) have potential tannins, total flavonoids and total phenolics as examined in vitro in the present study. In addition, the antioxidant effect of Egyptian sage (ESE) and fenugreek (FE) extracts were evaluated in normal male adult mice. Also, there is no evidence about the positive and/or negative effect of those extracts on male fertility. In order to evaluate the beneficial effect of those extracts, liver and kidney functions, lipid peroxidation, nitric oxide. In addition, non-enzymatic and enzymatic antioxidant molecules as glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), glutathione reductase (GR) and glutathione-S-transferase (GST) were estimated. Also, histological examination of testis was done. The results revealed that both extract of ESE and FE have potent antioxidant activity by reducing lipid peroxidation and nitric oxide formation in testis tissues of mice. Those activities were extended to non-enzymatic and enzymatic antioxidant defense components such as GSH, CAT, SOD, GR and GST. Additionally, ESE mixed to FE caused enhancement in testis structure with improved seminiferous tubules and spermatozoa. In conclusion, the results obtained showed that ESE and FE may contain some biologically active components that may be active against oxidative stress, and this may be the basis for its traditional use for environmental toxins.
Keywords: Salvia aegyptiaca,Trigonella foenum graecum, Antioxidant properties, Oxidants/antioxidants status, Mice.